Improvement of professional training of future specialists on studactive classes. - Oleksenko V.M; Oleksenko N.I (Kharkov National Pedagogical University, 2010)
The ways and means of realization of educational activity directed at improvement of professional training of future specialists are exposed in the article. The basic conditions of development of students' creative abilities are revealed. The dependence of knowledge quality and level of professional training of future specialists on the type of studies and technologies of their carrying out is grounded. The high efficiency of studactive classes in the process of such an activity is proved. It is established that the new type of classes has a huge educational potential.